Autologous non-myeloablative haematopoietic stem cell transplantation for refractory systemic vasculitis. Issue 7 (18th October 2007) - Statkute, L; Oyama, Y; Barr, W G; Sufit, R; Ho, S; Verda, L; Loh, Y; Yaung, K; Quigley, K; Burt, R K
Abstract : Objective: For patients with systemic vasculitis (SV) refractory to conventional therapy, new treatment strategies aimed at aggressive induction of remission and relapse prevention are being sought. We herein report our single-centre experience in treating four patients with refractory SV employing non-myeloablative autologous haematopoietic stem cell transplantation (HSCT). Methods: Four patients with refractory SV (two with neurovascular Behcet disease, one with neurovascular Sjögren syndrome, and one with Wegener granulomatosis) were involved in an Institutional Review Board (IRB) and US Food and Drug Administration (FDA) approved phase I clinical trial of high dose chemotherapy and autologous HSCT. Peripheral blood stem cells were mobilised with cyclophosphamide (Cy) and granulocyte-colony stimulating factor (G-CSF). Conditioning regimen consisted of Cy 200 mg/kg and rabbit anti-thymocyte globulin 5.5 mg/kg intravenously (iv). Results: All four patients tolerated HSCT well without transplant related mortality or any significant toxicity. At median follow-up of 28 (range 22–36) months all patients were alive. Three patients (one with Behcet disease, one with Sjögren syndrome, and one with Wegener granulomatosis) entered a sustained remission at 6, 6 and 24 months, respectively, after transplant. They had significant decrease in disease activity and disease or treatment related damage, as measured by the Birmingham Vasculitis Activity Score and Vasculitis Damage Index, respectively. All three patients who achieved remission discontinued immunosuppressive therapy at the time of transplant and have not required treatment since. One patient with Behcet disease and positive for human leukocyte antigen (HLA)-B51 has not improved after HSCT. Conclusion: We suggest non-myeloablative autologous HSCT is an alternative therapy for select patients with SV refractory to conventional immunosuppressive therapies.